Establishing the literature base of SWPBIS research in schools with large populations of underrepresented students. Issue 4 (3rd August 2020) - McDaniel, Sara C.; Bruhn, Allison L.; Peshak George, Heather
Abstract: For more than 20 years, the schoolwide positive behavioral interventions and supports (SWPBIS) literature base has been growing as it relates to implementation and sustainability across various settings and grade levels. While the research is clear that SWPBIS is an effective multitiered framework, gaps in the literature exist. Specifically, the extent to which SWPBIS has been implemented in traditionally underrepresented schools has yet to be fully examined. This systematic review of the SWPBIS literature base resulted in 46 articles that were coded across 13 variables. The number of articles highlight underrepresentation in the SWPBIS literature. Researchers demonstrated variable (a) reductions in rates of disciplinary infractions and exclusionary responses, (b) implementation with fidelity, and (c) positive student outcomes across academics, attendance, and achievement.